Design of a Small Quadruped Robot with Parallel Legs - Ming Lu; Baorui Jing; Hao Duan; Guanbin Gao (Complexity)
In this paper, a lightweight and modular design of a quadruped robot with two-degree-of-freedom parallel legs is presented. To reduce the weight and enhance the transmission accuracy, the horizontal layout of the driving end is adopted for designing the legs of the quadruped robot. The rotation angle of each actuator for the quadruped robot is analyzed by the inverse kinematics algorithm. Moreover, the trajectory of the foot-end, including support and swing phases, is planned to reduce the impact between the foot-end and the ground. Furthermore, the gait of the four legs of the quadruped robot is designed by considering the conditions of trot, standing, take-off, and walking. Finally, the effectiveness of the foot-end trajectory and the stable gait is verified by conducting experiments on a prototype platform.